Skeleto-muskular mechanism of the halteres of the melon fly, Dacus (Strumeta) cucurbitae Coquillett (Diptera: Trypetidae). - Zaka-ur-Rab, Md. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The skeleto-muscular mechanism of the halteres of the melon fly Dacus (Strumeta) cucurbitae Coquillett, has been described in detail which also happens to the first accound of its type in Diptera Cyclorrhapha. It has been shown thät the haltere is acted upon by a greater number of muscles than hitherto known. Comparison has been made with other dipterous insects where ever found possible.